STUDY ON VIBRATION FATIGUE CHARACTERISTICS OF SAFETY HANGER FOR METRO VEHICLE - ZHANG FuBing; WU PingBo; QU Sheng (Jixie qiangdu)
Aiming at analyzing the reason of damage of safety hanger on metro vehicle,the finite element model and modal test was conducted for modal analysis.Finally,the natural modes near 340 Hz and 990 Hz were obtained.At the same time,in order to obtain the acceleration and dynamic stress level of the safety hanger in the operation process,a line tracking test was performed on the vehicle.According to the test data,it was found that due to the presence of rail corrugation excitation,the energy of the dynamic stress and acceleration at 340 Hz increased sharply,which indicates that the first-order mode was excited to generate resonance.According to the dynamic stress data before and after the rail corrugation,the fatigue life of the safety hanger was evaluated and compared.It is found that the fatigue damage caused by the rail corrugation greatly shortens the service life of the safety hanger.